A comparative study of magnetic resonance imaging and arthroscopic findings in the diagnosis and management of meniscal lesions - Singh, Rakesh; Saran, Rajat; Singh, Nisha (International Journal of Research in Orthopaedics, 2025)
Background: Meniscal injuries are the most common types of knee injuries, particularly in athletes and individuals with physically demanding activities. Meniscal lesions can be assessed by either magnetic resonance imaging (MRI) or arthroscopy. There is a pressing need to compare the findings of MRI and arthroscopy to optimize the diagnostic process, which is critical in determining the most appropriate treatment, whether conservative or surgical. Methods: The aims of this study was to evaluate the MRI and arthroscopy findings in patients with meniscal injuries of knee joint and to compare and assess the clinical significance of MRI and arthroscopic findings in the management of Meniscal Injuries. Hospital based observational study conducted on 50 patients with knee injury ranging from 18 to 60 years after obtaining written informed consent. Participants recruited by non- probability convenience sampling. Those with local infections or neoplasms, those having contraindications to MRI and unfit for anaesthesia were excluded from the study. Data collected using semi- structured questionnaire after pilot testing. Data entered into Microsoft excel and analyzed using Stata 17.0. Diagnostic accuracy analysis viz., sensitivity and specificity assessments for MRI and arthroscopy were conducted. Results: Mean age of study participants was 34.6 years and 70% were males. Grade III meniscal tears were the most common (42%). The sensitivity and specificity of MRI was 89.6% and 100% respectively indicating that it correctly identified a high proportion of true meniscal tears and ruled out meniscal injury in all patients without tear. Conclusions: MRI is a highly accurate, non-invasive diagnostic tool for detecting meniscal injuries.